Remodeling of Epidural Fluid Hematoma after Uniportal Lumbar Endoscopic Unilateral Laminotomy with Bilateral Decompression: Comparative Clinical and Radiological Outcomes with a Minimum Follow-up of 2 Years - Pang Hung Wu; Hyeun Sung Kim; Giovanni Grasso; Jin Woo An; Myeonghun Kim; Inkyung Lee; Jong Seon Park; Jun Hyoung Lee; Sangsoo Kang; Jeongshik Lee; Yeonjin Yi; Jun Hyung Lee; et al. (Asian Spine Journal, 2023)
Study Design Retrospective cohort study. Purpose To evaluate the clinical and radiological effects of epidural fluid hematoma in the medium term after lumbar endoscopic decompression. Overview of Literature There is limited literature comparing the effect of postoperative epidural fluid hematoma after uniportal endoscopic decompression. Methods Magnetic resonance imaging (MRI) and clinical evaluation were performed for patients with single-level uniportal endoscopic lumbar decompression with a minimum follow-up of 2 years. Results A total of 126 patients were recruited with a minimum follow-up of 26 months. The incidence of epidural fluid hematoma was 27%. Postoperative MRI revealed a significant improvement in the postoperative dura sac area at postoperative day 1 and at the upper endplate at 6 months in the hematoma cohort (39.69±15.72 and 26.89±16.58 mm2) as compared with the nonhematoma cohort (48.92±21.36 and 35.1±20.44 mm2), respectively (p<0.05); and at the lower endplate on postoperative 1 day in the hematoma cohort (51.18±24.69 mm2) compared to the nonhematoma cohort (63.91±27.92 mm2) (p<0.05). No significant difference was observed in the dura sac area at postoperative 1 year in both cohorts. The hematoma cohort had statistically significant higher postoperative 1-week Visual Analog Scale (VAS; 3.32±0.68) pain and Oswestry Disability Index (ODI; 32.65±5.56) scores than the nonhematoma cohort (2.99±0.50 and 30.02±4.84, respectively; p<0.05). No significant difference was found at the final follow-up VAS, ODI, and MRI dura sac area. Conclusions Epidural fluid hematoma is a common early postoperative MRI finding in lumbar endoscopic unilateral laminotomy with bilateral decompression. Conservative management is the preferred treatment option for patients who do not have a neurological deficit. Symptoms last only a few days and are self-limiting. A common endpoint is a remodeled fluid hematoma and the subsequent expansion of the dura sac area.